Entre os discursos de fundamentação e os discursos de aplicação no direito da cisão à applicatio: um olhar a partir da crítica hermenêutica do direito - Sito, Santiago Artur Berger (Universidade do Vale do Rio dos Sinos, 2012)
In times of Contemporary Constitutionalism, this work comes with a timely and specific goal: to shed light on two proposals that arise within the emerging constitutionalism of the second postwar period, to ascertain how two theories of law, in a wide perspective (but that study the issues of interpretation and decision, in a certain way), analyze the problem left by the positivism(s). The proposal is understood within a philosophical paradigm basted with hermeneutic phenomenology, which disregards the methods (in the cartesian way) as a tool for finding the truth. And in doing so, at first, penetrates into a portion of what was done in this theoretical environment represented by the Contemporary Constitutionalism and its consequences in Brazil. In a second step, specifically two theories are studied: on one hand the proposal of Jürgen Habermas, Discoursive Theory of Law, which called moral propositions of Klaus Günther, a philosopher who works the question of the reasons/justification discourses and application discourses; on the other side to Critical Hermeneutics of Law, gathered by Lenio Luiz Streck, using in intakes of Hermeneutic Philosophy of Martin Heidegger, the Philosophical Hermeneutics of Hans-Georg Gadamer, and the Integrative Theory of Ronald Dworkin. Such investigations will allow a comparison in how the interpretation and understanding occur in both brands. Finally, to obtain a commitment to the theoretical context of today, assesses the relevance of the proposals, concluding that the hermeneutic contributions suggest a means of access to knowledge in law, more in line with advances in philosophy. In general, the work presents itself as an analysis tool that, when determining their bases, makes clear the place of speech, and with fidelity to the program, will the conditions of interpretation in the actual law-philosophical paradigm.
Keywords: Constitucionalismo contemporâneo; Teoria discursiva; Discursos de fundamentação/justificação; Discursos de aplicação; Crítica hermenêutica do direito; Contemporary constitutionalism; Discoursive theory of law; Reasons/justification discourses; Application discourses; Critical hermeneutics of law; ACCNPQ::Ciências Sociais Aplicadas::Direito